A New Tubular Graphene Form of a Tetrahedrally Connected Cellular Structure. (25th August 2015) - Bi, Hui; Chen, I‐Wei; Lin, Tianquan; Huang, Fuqiang
<x xml:space="preserve">Abstract</x> 3D architectures constructed from a tubular graphene network can withstand repeated >95% compression cycling without damage. Aided by intertubular covalent bonding, this material takes full advantage of the graphene tube's unique attributes, including complete pre‐ and post‐buckling elasticity, outstanding electrical conductivity, and extraordinary physicochemical stability. A highly connected tubular graphene will thus be the ultimate, structurally robust, ultrastrong, ultralight material.